Shelley and the Revolution in taste : the body and the natural world - Morton, Timothy, 1968- (New York : Cambridge University Press, 1994)
"This book brings together the themes of diet, consumption, the body, and human relationships with the natural world, in a highly original study of Shelley. A campaigning vegetarian and proto-ecological thinker, Shelley may seem to us curiously modern, but Morton offers an illuminatingly broad context for Shelley's views in eighteenth-century social and political thought concerning the relationships between humanity and nature. The book is at once grounded in the revolutionary history of the period 1790-1820, and informed by current theoretical issues and anthropological and sociological approaches to literature. Morton provides challenging new readings of much-debated poems, plays, and novels by both Percy and Mary Shelley, as well as the first sustained interpretation of Shelley's prose on diet. With its stimulating literary-historical reassessment of questions about nature and culture, this study will provoke fresh discussion about Shelley, Romanticism, and modernity."--Pub. desc
Introduction: prescriptions -- 1. The rights of brutes -- 2. The purer nutriment: diet and Shelley's biographies -- 3. In the face: the poetics of the natural diet -- 4. Apollo in the jungle: healthy morals and the body beautiful -- 5. Intemperate figures: re-fining culture -- 6. Sustaining natures: Shelley and ecocriticism.
Includes bibliographical references (pages 275-292) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Shelley, Percy Bysshe, -- 1792-1822 -- Political and social views; Shelley, Percy Bysshe, -- 1792-1822 -- Pensée politique et sociale; Shelley, Percy Bysshe, -- 1792-1822; Shelley, Percy Bysshe -- 1792-1822; Ernährung.; Shelley, Percy Bysshe; Human body in literature; Human-animal relationships -- Public opinion -- History -- 18th century; Nature conservation -- Public opinion -- History -- 18th century; Vegetarianism -- Public opinion -- History -- 18th century; Diet -- Public opinion -- History -- 18th century; Human-animal relationships in literature; Vegetarianism in literature; Nature in literature; Diet in literature; Romanticism; Human Body -- in literature; Diet, Vegetarian -- in literature; Public Opinion; Corps humain dans la littérature.; Relations homme-animal -- Opinion publique -- Histoire -- 18e siècle.; Nature -- Conservation -- Opinion publique -- Histoire -- 18e siècle.; Végétarisme -- Opinion publique -- Histoire -- 18e siècle.; Alimentation -- Opinion publique -- Histoire -- 18e siècle.; Relations humain-animal dans la littérature.; Végétarisme dans la littérature.; Nature dans la littérature.; Alimentation dans la littérature.; Romantisme; romanticism (form of expression); POETRY -- English, Irish, Scottish, Welsh; Diet in literature; Diet -- Public opinion; Human-animal relationships in literature; Human-animal relationships -- Public opinion; Human body in literature; Nature conservation -- Public opinion; Nature in literature; Political and social views; Romanticism; Vegetarianism in literature; Körper; Natur; Tiere; Vegetarismus; Geschmack; Vegetarisme; 1700-1799; History